The Difference between the optical coherence tomography (OCT) findings of newly progressed coronary lesions in symptomatic and asymptomatic patients. (1st November 2016) - Shiode, Nobuo; Okimoto, Tomokazu; Tamekiyo, Hiromichi; Kawase, Tomoharu; Yamane, Kenichi; Kagawa, Yuzo; Fujii, Yuto; Ueda, Yusuke; Hironobe, Naoya; Kato, Yasuko; Hayashi, Yasuhiko
Abstract: Background: Generally, newly progressed coronary lesions (NPCLs) are considered to be composed of lipid-rich plaques. In case of vulnerable plaque rupture, they may quickly become culprit lesions responsible for acute coronary syndromes. Methods: Between September 2011 and September 2015, 2034 patients underwent scheduled follow-up coronary angiography (CAG) after percutaneous coronary intervention (PCI) in Tsuchiya General Hospital. Patients with NPCLs found by CAG during the follow-up period were evaluated by optical coherence tomography (OCT). NPCLs were defined as the lesions with less than 50% diameter stenosis, which progressed to more than 75% diameter stenosis within 3 years after the previous CAG. Patients with restenosis after PCI were excluded. We compared OCT findings of NPCLs between symptomatic and asymptomatic patients. Results: The follow-up CAG showed NPCLs in 64 patients (3.2%). OCT revealed fibrous plaque in 42 patients (65.6%) and thin-cap fibroatheroma in one patient. Thirteen patients had chest symptoms for one month before CAG and the remaining 51 patients were asymptomatic. The prevalence of fibrous plaque and intimal disruption or plaque rupture were not significantly different between symptomatic and asymptomatic patients (61.5% vs. 66.7%, p = 0.752 and 30.8% vs. 11.8%, p = 0.213, respectively). However, thrombi were more frequently observed in symptomatic patients (61.5% vs. 13.7%, p < 0.001). Conclusions: The majority of NPCLs found in asymptomatic patients at follow-up CAG were not vulnerable; however, those found in symptomatic patients might be vulnerable. In clinical practice, NPCLs found in asymptomatic patients should be evaluated for functional severity of stenosis in order to determine the need for coronary revascularization.